2006
DOI: 10.4269/ajtmh.2006.74.41
|View full text |Cite
|
Sign up to set email alerts
|

Cd4 T Cell Activation as a Predictor for Treatment Failure in Ugandans With Plasmodium Falciparum Malaria

Abstract: Host immunity plays an important role in response to antimalarial therapy but is poorly understood. To test whether T cell activation is a risk factor for antimalarial treatment failure, we studied CD4(+) and CD8(+) T cell activation in 31 human immunodeficiency virus-negative Ugandan patients 5-37 years of age who were treated for uncomplicated Plasmodium falciparum malaria. Increased CD4(+) T cell activation, as indicated by co-expression of HLA-DR and CD38, was an independent risk factor for treatment failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Acute malaria infection may also be associated with an enhanced cellular activation state. Co-expression of CD38/HLA-DR on T cell subsets has previously been studied in both HIV-1/AIDS or malaria alone (Hunt et al 2003, Eggena et al 2006, Naniche et al 2011) and immune activation was considered a predictor of treatment failure in malaria patients (Eggena et al 2006). Malaria infection can present with a pro-inflammatory response and cytokine imbalance (Ayimba et al 2011, Davenport et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Acute malaria infection may also be associated with an enhanced cellular activation state. Co-expression of CD38/HLA-DR on T cell subsets has previously been studied in both HIV-1/AIDS or malaria alone (Hunt et al 2003, Eggena et al 2006, Naniche et al 2011) and immune activation was considered a predictor of treatment failure in malaria patients (Eggena et al 2006). Malaria infection can present with a pro-inflammatory response and cytokine imbalance (Ayimba et al 2011, Davenport et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of activation markers provides a general assessment of the extent to which a pathogen activates the immune system (Eggena et al 2006). In the present study, we evaluated the expression levels of CCR5, CD25, and CD95 on CD4+ T cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In CHMI studies, we have shown that the control of the parasite in malaria‐naïve volunteers following the infection with P. falciparum ‐infected red blood cells (pRBCs) is associated with the expansion of a population of CD4 + T cells co‐expressing the activation marker CD38 8 . However, in naturally exposed individuals from Uganda, an increased frequency of CD38‐expressing CD4 + T cells predicts treatment failure 9 , and in another study, CD38 + CD4 + T‐cell frequency correlated positively with HIV viral load, which was further accentuated in patients co‐infected with malaria 10 .…”
Section: Introductionmentioning
confidence: 99%